2006
DOI: 10.3892/or.15.3.615
|View full text |Cite
|
Sign up to set email alerts
|

Frequent p16 CpG island hypermethylation in primary remnant gastric cancer suggesting an independent carcinogenic pathway

Abstract: Cancer found in the post-operative remnant stomach includes both newly developed cancer after surgery for benigndisease (PRC) and metachronous multiple cancer (MRC). Differences in the carcinogenic pathway between PRC and MRC have been suspected from clinical studies. However, no study has demonstrated the difference in molecular alteration between these diseases. P16 is inactivated predominantly by epigenetic change, rather than genetic alteration. We analyzed the methylation status and protein expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…However, they studied only one gene in each report which gives limited insight into DNA hypermethylation across the whole genome. Our results may contradict that of Mino et al [18] since we found that overall PGC promoter methylation is higher than in RGC. Our findings, however, are corroborated by (1) the RMVs in normal-appearing adjacent non-cancerous tissues in PGC were also significantly higher than those in RGC;+ (2) cancer tissues in RGC demonstrated significantly higher RMVs in three genes (except for TNFRSF10B) than those in normal-appearing adjacent non-cancerous tissues in RGC.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, they studied only one gene in each report which gives limited insight into DNA hypermethylation across the whole genome. Our results may contradict that of Mino et al [18] since we found that overall PGC promoter methylation is higher than in RGC. Our findings, however, are corroborated by (1) the RMVs in normal-appearing adjacent non-cancerous tissues in PGC were also significantly higher than those in RGC;+ (2) cancer tissues in RGC demonstrated significantly higher RMVs in three genes (except for TNFRSF10B) than those in normal-appearing adjacent non-cancerous tissues in RGC.…”
Section: Discussioncontrasting
confidence: 99%
“…Their study demonstrated similar results to ours in terms of higher gene methylation rates in three genes in cancer tissues compared with normal-appearing adjacent non-cancerous tissues. Mino et al [18] investigated p16 gene methylation of cancer tissues with qualitative MSP in two separate analyses for those RGCs which had newly developed after surgery performed either for benign disease or for gastric cancer. They concluded that p16 gene hypermethylation was found more frequently in RGC which developed after surgery for benign disease than in PGC or in RGC which developed after surgery for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is a well recognized epigenetic mechanism in the regulation of gene expression (1)(2)(3)(4). Methylation inhibits gene expression directly by interfering with transcription factor binding and/or indirectly by recruiting histone deacetylases through methyl-DNA-binding proteins (5).…”
Section: Introductionmentioning
confidence: 99%
“…For the CpG sites in the enhancer and promoter regions, the methylation proportion was lowest in cervical swab DNA samples from patients with normal tissue/LSIL, and highest in those with CC. Previous studies have demonstrated that methylation is able to regulate gene expression as an epigenetic mechanism (31)(32)(33). Numerous transcription factor binding sites in the HPV 16 enhancer and promoter regions contain CpG sites (19).…”
Section: Discussionmentioning
confidence: 99%